The impact of South African culture on the work-life balance of women in leadership positions - Nehemia, Naong Matsidiso; Lenkoe, Naong Mammako (International Journal of Innovative Research and Scientific Studies, 2023)
Women are the pillars of every healthy society. Numerous socio-cultural practices, especially patriarchy and religion in African communities deprive women of equality and justice across all sectors of society. However, younger and educated generations seem to adopt a different attitude. This paper explores the impact of South African culture and the work-life balance (WLB) of women in managerial positions since the democracy’s inception. A survey based on elements of three complementary theories: the role of congruity, feminism and cultural dimension theories was used to collect data from 187 women in leadership positions in the Mangaung metropolitan municipality in the Free State province of South Africa giving a 75% return rate. A factor analysis was conducted to determine the loading of items. The reliability of instruments using the Cronbach alpha value was reported at 0.87. Results reveal that 47.1% bemoan cultural tendencies at work. Furthermore, 35.7% opined that the choice between adoption and conceiving children is non-negotiable, despite pressing work demands and 34.3% agreed that culture makes them feel guilty if they give their work preference over their family life. Crafting human resource strategies that advocate for ‘gender equality or sensitivity’ and harmonise the work-life balance of female staff in order to enhance their performance in a sustainable way is long overdue and needs to be prioritized by any South African organizations.